2015
DOI: 10.1007/s00382-015-2664-4
|View full text |Cite
|
Sign up to set email alerts
|

Climate change projections for CORDEX-Africa with COSMO-CLM regional climate model and differences with the driving global climate models

Abstract: the reduced spread in the results when a single RCM is used for downscaling, we strongly emphasize the importance of exploiting fully the CORDEX-Africa multi-GCM/ multi-RCM ensemble in order to assess the robustness of the climate change signal and, possibly, to identify and quantify the many sources of uncertainty that still remain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
78
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(88 citation statements)
references
References 55 publications
10
78
0
Order By: Relevance
“…Our results correspond to the work by Dosio & Panitz (2016) showing that rising temperatures simulated by an RCM ensemble using a RCP4.5 and RCP8.5 emission scenarios lead to increasing numbers of warm nights (90th percentile) in the CORDEX-Africa region. Russo et al (2016) found in 50% of regional climate projections applying RCP8.5 emission scenario HWs, which are unusual under the present climate and become regular by 2040 (i.e., under higher temperatures).…”
Section: /2017ef000714supporting
confidence: 90%
See 1 more Smart Citation
“…Our results correspond to the work by Dosio & Panitz (2016) showing that rising temperatures simulated by an RCM ensemble using a RCP4.5 and RCP8.5 emission scenarios lead to increasing numbers of warm nights (90th percentile) in the CORDEX-Africa region. Russo et al (2016) found in 50% of regional climate projections applying RCP8.5 emission scenario HWs, which are unusual under the present climate and become regular by 2040 (i.e., under higher temperatures).…”
Section: /2017ef000714supporting
confidence: 90%
“…We set our regional focus over the African continent as Africa is supposed to be a climate change hot spot with a high exposure to future climate changes and a low adaptation capacity resulting in a very large vulnerability to future climate change (e.g., Intergovernmental Panel on Climate Change Fifth Assessment Report). and have been analyzed and published in coordinated ways within the CORDEX-Africa initiative (e.g., Abba Omar & Abiodun, 2017;Abiodun et al, 2017;Diallo et al, 2016;Dosio, 2017;Dosio & Panitz, 2016;Fotso-Nguemo et al, 2017;Pinto et al, 2016;Sylla et al, 2016). Examples are the widely spread rainfed agricultural systems, the fragile infrastructure, and various health issues related to climate such as malnutrition after droughts, heat waves (HWs), but also malaria outbreaks (e.g., Kjellstrom et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In opposite, the decreasing trends for annual total precipitation (−12 mm/year), the number of heavy (−4.32 days/year) and very heavy precipitation days (−2.7 days/year), the maximum of consecutive wet days have showed the significant for most stations following the RCP8.5 scenario. These results are in line with Dosio and Panitz [55] using the regional climate model CCLM, have predicted a significant reduction of precipitation at the end of the century in West Africa. It is also in line with the recent special IPCC report which states that West Africa will likely experience longer and more intense droughts in the near future [56].…”
Section: Discussionsupporting
confidence: 80%
“…The models' disagreement remains unresolved in phase 5 of the coupled model intercomparison project (CMIP5) despite significant improvements of the models in many aspects [IPCC, 2013;Nicholson, 2013;Biasutti, 2013]. On the other hand, Regional Climate Models (RCMs) tend to produce more consistent projections for WA, in spite of the considerable disagreements among the driving GCMs [Patricola and Cook, 2010;Buontempo et al, 2015;Dosio and Panitz, 2016]. This is mainly attributed to the RCMs physics dominating over the signal imposed by large-scale forcing over WA, and to a lesser extent, the coarse representation of surface conditions in the GCMs being unable to capture the heterogeneous topography, land cover, and For RCM applications, the common approach of prescribing a static land cover is considered a major limitation.…”
Section: Introductionmentioning
confidence: 99%